Caregivers' concerns about the sexual and reproductive health of women with intellectual disability in Iran: a qualitative study - Ziba Taghizadeh; Maryam Farmahini Farahani; Malihe Nourollahpour Shiadeh; Kowsar Qaderi (BMC, 2024)
Abstract Background Women with intellectual disability (ID) have many sexual and reproductive problems. This study was conducted to explain the sexual and reproductive health considerations of women with ID from the perspective of their caregivers in a qualitative approach. Methods This study was a qualitative research conducted with a content analysis approach in Iran. The sampling method used was targeted sampling with maximum possible variation, which was continued until data saturation. For data collection, in-depth and semi-structured interviews were conducted with 21 participants, including 8 mothers, 6 caregivers, and 7 specialist caregivers who had experience working with women with intellectual disabilities. Data analysis was conducted using the conventional content analysis method proposed by Zhang and Wildemuth. Results Two main themes, four categories and 12 subcategories emerged from the data analysis. The themes include "Reproductive health concerns" and" "Sexual health concerns". This means that this group of women has many problems with menstrual hygiene and vaginal infections. On the other hand, caregivers were concerned about the manifestations of unconventional sexual behaviors and difficulties in controlling sexual behaviors as well as the risk of sexual abuse. Conclusion The results of the present study show that it is not only necessary to provide women with ID with practical instructions on menstrual hygiene and sexual self-care, but also that regular examinations of the reproductive system by obstetricians or midwives, especially in care centers, seem essential.